Stress response of methanogenic archaea from Siberian permafrost compared to methanogens from non-permafrost habitats - Morozova, Daria; Wagner, Dirk (FEMS Microbiology Ecology, 2007)
We examined the survival potential of methanogenic archaea exposed to different environmental stress conditions such as low temperature (down to 78.5 °C), high salinity (up to 6 M NaCl), starvation (up to 3 months), long-term freezing (up to 2 years), desiccation (up to 25 days) and oxygen exposure (up to 72 hours). The experiments were conducted with microbial populations of methanogenic archaea from Siberian permafrost and were complemented by experiments on well-studied methanogens from non-permafrost habitats. Our results indicate a high survival potential of a methanogenic archaeon from Siberian permafrost when exposed to the extreme conditions tested. In contrast, these stress conditions were lethal for methanogenic archaea isolated from non-permafrost habitats. A better adaptation to stress was observed at a low temperature (4 °C) compared to a higher one (28 °C). Given the unique metabolism of methanogenic archaea in general and the long-term survival and high tolerance to extreme conditions of the methanogenic archaeon investigated in this study, methanogenic archaea from permafrost should be considered as primary candidates for possible subsurface Martian life.